Multiwavelength observations of PSR J2032+4127 during the 2017 periastron passage - Chernyakova M; Malyshev D; Blay P; van Soelen B; Tsygankov S (OXFORD UNIV PRESS, 2022)
PSR J2032+4127 is only the second known gamma-ray binary where it is confirmed that a young radio pulsar is in orbit around a Be-star. The interaction of the pulsar wind with the mass outflow from the companion leads to broad-band emission from radio up to TeV energies. In this paper we present results of optical monitoring of the 2017 periastron passage with the Nordic Optical Telescope. These observations are complemented by X-ray (Swift/XRT, NuSTAR) and GeV (Fermi/LAT) monitoring. Joint analysis of the evolution of the parameters of the H alpha line and the broad-band (X-ray to TeV) spectral shape allows us to propose a model linking the observed emission to the interaction of the pulsar and Be-star winds under the assumption of the inclined disc geometry. Our model allows the observed flux and spectral evolution of the system to be explained in a self-consistent way.